The c-myc and PyMT oncogenes induce different tumor types in a somatic mouse model for pancreatic cancer - Lewis, Brian C. (Cold Spring Harbor Laboratory Press, 2003)
We have generated a mouse model for pancreatic cancer through the somatic delivery of oncogene-bearing avian retroviruses to mice that express TVA, the receptor for avian leukosis sarcoma virus subgroup A (ALSV-A), under the control of the elastase promoter. Delivery of ALSV-A-based RCAS vectors encoding either mouse polyoma virus middle T antigen (PyMT) or c-Myc to elastase-tv-a transgenic, Ink4a/Arf null mice induced the formation of pancreatic tumors. RCAS-PyMT induced pancreatic tumors with the histologic features of acinar or ductal carcinomas. The induced pancreatic lesions express Pdx1, a marker for pancreas progenitor cells, and many tumors express markers for both exocrine and endocrine cell lineages, suggesting that the tumors may be derived from progenitor cells. In contrast, RCAS-c-myc induced endocrine tumors exclusively, as determined by histology and detection of differentiation markers. Thus, specific oncogenes can induce the formation of different pancreatic tumor types in a single transgenic line, most likely from one or more types of multipotential progenitor cells. Our model appears to be useful for elucidating the genetic alterations, target cells, and signaling pathways that are important in the genesis of different types of pancreatic cancer.